Forsyth Country Club swimming pool, 1924. - Unknown (Forsyth County Public Library, 1924)
Source: Booklet, "Art Work of Piedmont Section of North Carolina, " 1924.
Forsyth Country Club swimming pool, 1924.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth